Applications of Super Resolution Expansion Microscopy in Yeast - Chen, Liwen; Yao, Longfang; Zhang, Li; Fei, Yiyan; Mi, Lan; Ma, Jiong (Frontiers in Physics, 2021)
Super-resolution microscopy includes multiple techniques in optical microscopy that enable sub-diffraction resolution fluorescence imaging of cellular structures. Expansion microscopy (EXM) is a method of physical expansion to obtain super-resolution images of a biological sample on conventional microscopy. We present images of yeast organelles, applying the combination of super-resolution and ExM techniques. When preparing pre-expanded samples, conventional methods lead to breakage of dividing yeast cells and difficulties in studying division-related proteins. Here, we describe an improved sample preparation technique that avoids such damage. ExM in combination with Airyscan and structured illumination microscopy (SIM) collected sub-cellular structural images of nuclear pore complex, septin, and a-tubulin in yeast. Our method of expansion in yeast is well-suited for super-resolution imaging study of yeast.